Kedudukan Harta Bersama dalam Perkawinan Campuran Antara Warga Negara Indonesia dan Warga Negara Asing - Annisa Pebrina Harahap; Hening Hapsari Setyorini (UNES Law Review, 2023)
Marriage is a form of cooperation between a man and a woman in society under special regulations and this is taken into account by religion, state, and custom. In general, marriage is a process of uniting two different individuals into a husband and wife with the aim of building a household and strengthening brotherhood between families. Marriage not only concerns the individual of husband and wife but also concerns all family and community matters. The definition of marriage based on the provisions of Article 1 of Law Number 1 of 1974 concerning Marriage states that "Marriage is an inner and outer bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family or household based on the belief in the Almighty God." Marriages can be carried out with different nationalities which are called mixed marriages. Article 57 Law no. 1 of 1974 Mixed Marriage is a marriage between two people who in Indonesia are subject to different laws, due to differences in nationality. The consequences of mixed marriages can have an impact on the status of children and marital assets because each country has its policies regarding mixed marriages and citizenship. In addition to containing matters related to marriage, the Marriage Law regulates marital property. This field is one of the areas of civil law with a sensitive nature and the potential to cause conflict because regulating this field is not as easy as regulating neutral legal fields. The complexity of problems in the area of ​​wealth resulting from mixed marriages, apart from being based on the Marriage Law No. 1 of 1974, also deals with the principles of International Private Law.